Temporal dynamics of probiotic Lacticaseibacillus casei and rhamnosus abundance in a fermented dairy product evaluated using a combination of cultivation-dependent and -independent methods. (August 2021) - Berezhnaya, Yulia; Bikaeva, Irina; Gachkovskaia, Anastasiia; Demidenko, Artem; Klimenko, Natalia; Tyakht, Alexander; Volokh, Olesya; Alexeev, Dmitry
Abstract: Benchmark of cost-efficient and accurate methods for quantifying probiotics in dairy products represents great interest to the food industry. The advantages of cultivation-independent techniques over the traditionally used cultivation-based ones are to be investigated in this context. We evaluated the levels of Lacticaseibacillus casei and rhamnosus in multiple formulations of a fermented dairy product fortified with these probiotics during the shelf-life using cultivation, taxon-specific qPCR augmented with propidium monoazide (PMA) viability test and 16S rRNA gene sequencing. The analyzed products were the yogurts produced with traditional yogurts starter cultures including Bifidobacteria or without them. The effect of the starter culture on probiotics viability and abundance was assessed. The methods for probiotic profiling were compared. All methods confirmed high levels for the probiotics throughout the shelf-life. The PMA-qPCR showed that their non-viable proportion was low. The formulations with the starter cultures including Streptococcus and Lactobacillus were associated with a lower abundance of each probiotic compared to those that additionally had Bifidobacterium in the starter culture. The total microbial composition according to the sequencing was generally as expected, but the method was of limited use for profiling the probiotic levels due to the data compositionality and dominance of the starter culture taxa. Highlights: Total microbiome and presence of each probiotic were stable during the shelf-life. No evidence of competition between Lacticaseibacillus casei and rhamnosus was found. The levels of probiotics are linked to the taxonomic diversity of starter culture. The application of 16S rRNA sequencing for quantifying probiotics in food is limited.